Pengaruh Pemahaman Orangtua Tentang Pendidikan Dan Profesionalisme Guru Terhadap Minat Baca Al-qur’an Siswa SMP Islam Al-Kautsar Pondok Cabe Ilir Tangerang Sela - Syamsul Bahri Tanrere; EE Junaedi Sastradiharja; Ahmad Mustaqim (Kopertais Wilayah I DKI Jakarta dan Banten, 2020)
This study aims to determine the effect of parents' understanding of education and professionalism of teachers on the reading interest of the Koran of Islamic Al-Kautsar Junior High School Islamic School Pondok Cabe Ilir, South Tangerang. This research is a quantitative study, with a population of all VII and VIII grade students (180 students), and a sample of 124 students. The sampling technique uses a questionnaire / questionnaire. Analysis of the data used is multiple linear regression analysis. The results of this study indicate that: 1) There is a positive and significant effect of education on the reading interest of the Koran of Al-Kautsar Islamic Junior High School students at Pondok Cabe Ilir, South Tangerang; 2) There is a positive and significant influence of teacher professionalism on the reading interest of al-Qur'an at Al-Kautsar Islamic Middle School Pondok Cabe Ilir South Tangerang students; 3) There is a positive and significant influence of teacher education and professionalism on the reading interest of al-Qur'an at Islamic Al-Kautsar Middle School Pondok Cabe Ilir, South Tangerang.